Determinantes of AFP demand in Chile: New empirical evidence from individual data - Berstein, Solange (Estudios de Economía, 2016)
This article is the first one to use individual data to analyze the demand for AFP in Chile. This study implements panel data techniques which allow us to estimate the switch probability of an AFP customer. Results confirm the fundamental role of sales agents, which was already suggested by previous studies that have used aggregated data by AFP. Particularly, we show that although price and return elasticity of demand are low, it raises notably when associated to a sales agent visit.